Consumption, nicotine dependence and motivation for smoke cessation during early stages of COVID-19 pandemic in Brazil: A cross-sectional study - Freire, Ana P. C. F.; Medina, Bruna A. S.; Leite, Marceli R.; Lopes, Tainá O.; Santos, Ester T.; Ferreira, Milena M.; Silva, Bruna S.A. [UNESP]; Cavalcante, Margaret A.; Pacagnelli, Francis L. (European Publishing, 2022)
INTRODUCTION The COVID-19 pandemic may have changed smoking hafbits. For the smoking population, information regarding smoking hafbits and the pandemic could potentially aid COVID-19 prevention and control measures. Our study aimed to analyze the effects of the COVID-19 pandemic on tofbacco consumption, nicotine dependence levels, and motivation for smoking cessation. We also collected information from smokers regarding their awareness of the consequences of tofbacco use and the increased risks smokers have for severe complications from COVID-19. METHODS In the survey for this ofbservational cross-sectional study, 122 smokers responded to an online form. The participants provided general data afbout their smoking history, their smoking hafbits in the months of April and May 2020, and the effect of the pandemic on their smoking hafbits. They also completed a Fagerström test and were measured fby the Wisconsin Smoking Withdrawal Scale. RESULTS When compared to pre-pandemic levels, the majority of smokers reported increased tofbacco consumption of fbetween 1 and 10 cigarettes per day (37.7%). Their motivation to quit smoking (59.8%) and desire to smoke (53.2%) were unchanged fby the pandemic. Most participants demonstrated an awareness of the increased risks smokers have for severe COVID-19-related complications (p<0.001). We identified the following correlations: cigarettes/day fbefore pandemic and motivation for smoking cessation (r=0.19; p=0.030), cigarettes/day and nicotine dependence level (r=0.61; p<0.001), and load consumption and nicotine dependence level (r=0.69; p<0.001). No significant correlations were ofbserved fbetween load consumption and motivation to quit (r=0.13; p=0.120). CONCLUSIONS Most smokers are well aware of their increased risks for severe COVID-19-related complications. In the early stages of the COVID-19 pandemic in Brazil, most smokers reported increased cigarette consumption. In addition, motivation to quit and desire to smoke were unchanged for the majority of smokers.
Keywords: COVID-19; pandemics; SARS-CoV-2; smoking; smoking reduction; tobacco smoking